Analysis of Ground Cover Vegetation on Soil Chemical Properties at PT Cibaliung Tunggal Plantation, Cibaliung I Palm Oil Plantation, Rokan Hilir Regency, Riau Province - Putra Rahmadani; Ingrid Ovie Yosephine (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The productivity of oil palm (Elaeis guineensis Jacq.) is strongly influenced by the chemical fertility of the soil, which can be maintained or enhanced through the presence of ground cover vegetation. This study aims to analyze the effects of different types of ground cover vegetation on soil chemical properties in the Cibaliung I Estate Plantation of PT. Cibaliung Tunggal Plantation, Rokan Hilir, Riau. The research employed a survey method with purposive soil sampling at 0–30 cm depth across three distinct land conditions: areas covered with Nephrolepis biserrata, areas covered with Ottochloa nodosa, and open land without vegetation. Soil chemical properties tested in the Palm Oil Research Center (PPKS) laboratory included soil pH, total nitrogen (Total N), available phosphorus (Available P), and organic carbon (Organic C). Laboratory analysis revealed that ground cover vegetation significantly improves and maintains soil chemical quality compared to open land without vegetation. Areas covered with Nephrolepis biserrata exhibited the highest soil pH value of 5.4 (slightly acidic), attributed to its high biomass production, which suppresses leaching of soil bases, compared to more acidic land without vegetation (pH 4.6). Meanwhile, areas with Ottochloa nodosa were most effective at enhancing soil nutrient and organic matter fertility, recording the highest Total N value of 0.60% and the highest Available P concentration of 69.39 ppm, likely due to biomass decomposition and root-microenvironment activity. In contrast, open land without vegetation showed the lowest fertility, with a Total N value of only 0.08% and very low Available P (<0.01 ppm), resulting from high risks of surface erosion and nutrient leaching. This study concludes that the management and maintenance of ground cover vegetation such as Nephrolepis biserrata and Ottochloa nodosa are essential components of a sustainable soil conservation strategy in oil palm plantations. Ground cover vegetation plays a crucial role in maintaining and improving soil quality, thereby supporting sustainable oil palm plantation management.